POSITIVE AND NORMATIVE ACCOUNTING THEORY: Definition and Development - Patty, Thadeus Fransesco Quelmo; Lamawitak, Paulus Libu; Goo, Emilianus Eo Kutu; Herdi, Henrikus (CV ODIS, 2021)
This study aims to explain the definition rather than accounting theory, in this case, it is more focused on normative accounting theory and positive accounting theory. The author uses various sources, both from previous research journals and from articles on the internet. The conclusion of this research is that theory is often used as the basis for an action or practice. The development of accounting theory was initiated by the writings of Patton and Littleton (1940) entitled An Introduction to Corporate Accounting Standards. The result of normative accounting theory is a statement or proposition that requires or requires in accounting practice, normative accounting theory focuses on prescriptions (norms) and is not intended for theory development. While positive accounting theory seeks to explain and predict phenomena related to accounting. By using an approach that comes from positivism, empirical accounting research is developed to support and justify various accounting methods or practices in the real world. There are four periods of accounting theory, starting with the Pre-Theory period from 1492-1800. Then continued with the Pragmatic accounting period (general scientific period) from 1800-1955. The period 1956-1970 is labeled the 'normative period'. The last is the period of positive accounting theory from 1970 to the present.